Innovative Grouting Process Monitoring: Design and Implementation of a Measurement Device With Datalogger Function - Gabriel Gaspar; Roman Budjac; Stefan Sedivy; Maximilian Stremy; Denis Benka; Eduard Nemlaha; Rastislav Elias (IEEE Access)
Recording data from processes and activities has become indispensable for quality assurance and process verification, serving as a cornerstone in achieving research objectives. This requirement is particularly significant in the construction industry, where modern grouting techniques are used for waterproofing during tunnel wall renovations to safeguard structures from capillary water ingress, which is vital for their durability. Detailed documentation of grouting processes is often necessary, as these records offer valuable insights into substrate conditions and grouting quality. This paper focuses on designing and implementing a device that captures physical data during the grouting process and stores it in a defined format on a microSD card. The paper covers problem analysis, key input variables identification, and suitable hardware components selection. The proposed device is versatile, enabling real-time monitoring of the grouting process, and can be adapted to measure the consumption of other materials, such as one- or two-component paints. The device underwent rigorous testing under laboratory conditions to ensure its functionality and reliability, and thus significantly contributes to the control and responsiveness of the grouting process by providing real-time data on critical operational parameters. In addition to the controlled testing, the device prototype was subjected to real-world testing during a major grouting project at the Bratislava-Lamač railway tunnel in the Slovak republic. This large-scale construction site provided a valuable opportunity to assess the device’s performance under operational conditions.